PENGEMBANGAN PINANG SEBAGAI TANAMAN ALTERNATIF DAN PENDUKUNG PENDAPATAN PETANI KELAPA SAWIT DI KABUPATEN ACEH BARAT - Aswin Nasution (Jurnal Bisnis Tani, 2020)
Palm oil plants as a superior crop in West Aceh District have recently experienced a shock with the decline in FFB prices due to international, national and local issues regarding palm oil trading. Preventive efforts to overcome this need to be done early by choosing alternative plants and supporting farmers' income, namely areca nut plants. The results showed that the development of areca palm as an alternative plant and oil palm supporting plants in West Aceh District should be focused on the fields of cultivation, industry, marketing and institutional farmers that are carried out in an integrated manner, not partially.